Giant Hepatic Cyst with Septal Structure: Diagnosis and Management. (29th May 2013) - Sato, Toshihiro; Imai, Michitaka; Hayashi, Kazunao; Isokawa, Osamu; Nomura, Tatsuya; Tsuchiya, Yoshiaki; Kawasaki, Takashi
Abstract : The hepatic cyst is a common benign liver tumor, and no surgical treatment is necessary. However, it is difficult to correctly diagnose the giant hepatic cyst containing the solid septal structures inside, from the malignant cystadenocarcinomas. The various imaging modalities such as computed tomography, magnetic resonance imaging, and ultrasonography, have been developed and are useful for the diagnosis of these liver tumors. Reviewing the other reports in this paper, the combination of more than 2 modalities will help to diagnose these tumors; however, the malignant potential is unable to be excluded if the tumor is huge. Therefore, the surgical resection should be considered for the huge hepatic cysts with septal structures if the correct diagnosis is unable to be made. For example, when the hemorrhages cause the granulation in the septa which often shows neovascularization, the imaging modalities are unable to define this situation from the malignant tissue with hypervascularity. Therefore, with the careful review of other reports, we conclude that if the imaging studies show the possible malignant potential or the sizing-up is marked, the surgical treatment should be considered with the consent from the patients.